2007
DOI: 10.1080/17482960701374643
|View full text |Cite
|
Sign up to set email alerts
|

Psychological health in patients with amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a progressive and fatal neurodegenerative disease with no known effective treatment or cure. Clinicians often expect that ALS patients will experience depression following the diagnosis because ALS is a terminal disease. The objective of the current study was to examine the evidence from the literature on psychological health in ALS patients in order to determine the prevalence and severity of depression in this population. Twenty-eight studies of ALS patients, conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
44
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 74 publications
6
44
0
1
Order By: Relevance
“…Reduced physical activity has a negative influence on mental health [33], although data on mood disorders in NMDs are inconsistent. These diseases are often accompanied by psychological distress that in many cases does not satisfy the criteria of clinical depression [2]. Patients with NMDs in our study, as well as those in the study by Kalkman et al [21], had a significantly reduced HRQoL in the SF-36 domains ''mental health'' and ''role limitations due to emotional problems''.…”
Section: Discussionsupporting
confidence: 45%
“…Reduced physical activity has a negative influence on mental health [33], although data on mood disorders in NMDs are inconsistent. These diseases are often accompanied by psychological distress that in many cases does not satisfy the criteria of clinical depression [2]. Patients with NMDs in our study, as well as those in the study by Kalkman et al [21], had a significantly reduced HRQoL in the SF-36 domains ''mental health'' and ''role limitations due to emotional problems''.…”
Section: Discussionsupporting
confidence: 45%
“…18 Previous studies rarely examined the temporal pattern of depression prevalence and were mostly based on small numbers of patients (range 27-131). [6][7][8][9][10][11][12][13][19][20][21] A recent meta-analysis identified a total of 3,190 patients with ALS from 103 studies on ALS and depression, 22 whereas in the present study, we were able to enroll 1,752 patients in a single study.…”
Section: Discussionmentioning
confidence: 92%
“…Multiple studies have shown that patients with ALS are more likely to develop depression than ALS-free individuals, although the reported prevalence of depression varies greatly. [6][7][8][9][10][11][12][13] Different measurements of depression together with the varying representativeness of the patient samples used in previous studies may partly explain the different prevalences reported so far.…”
mentioning
confidence: 99%
“…Systematic reviews concluded that major depression is uncommon, affecting between 6 and 12% of patients [12,13]. Recent studies report estimates of 6% for major and 29% for mild depression [14], of 22% for major and minor depression altogether [15].…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of antidepressant medication (ATDs) use was not common practice. Not accounting for the use of ATDs may underestimate depression [12]. When assessed, the prevalence of use ranged from 4 to 38% [7,14,16,17,18,22,23,24].…”
Section: Introductionmentioning
confidence: 99%